Recognition of a Face in a Mixed Document - Lhoussaine Bouhou; Rachid El Ayachi; Mohamed Fakir; Mohamed Oukessou (Institute of Advanced Engineering and Science, 2015)
Face recognition is the field of great interest in the domaine of research for several applications such as biometry identification, surveillance, and human-machine interaction…This paper exposes a system of face recognition. This system exploits an image document text embedding a color human face image. Initially, the system, in its phase of extraction, exploitis the horizontal and vertical histogram of the document, detects the image which contains the human face. The second task of the system consists of detecting the included face in other to determine, with the help of invariants moments, the characteristics of the face. The third and last task of the system is to determine, via the same invariants moments, the characteristics of each face stored in a database in order to compare them by means of a classification tool (Neural Networks and K nearest neighbors) with the one determined in the second task for the purpose of taking the decision of identification in that database, of the most similar face to the one detected in the input image.